Building Capacity in Post-Conflict Countries - McKechnie, Alastair J. (World Bank, Washington, DC, 2012)
This brief looks at the challenge of building capacity in post-conflict countries, reviews options for creating capacity, and identifies trade-offs between a rapid result and longer-term impacts of capacity strategies. Six lessons for more sustainable approaches to capacity building are identified: (a) leadership matters, (b) incentives also matter, (c) build on what exists, (d) arrange learning activities within a country wherever possible, (e) training needs to be defined in its strategic capacity, and (f) training should build on the comparative advantage of international partners.